2021
DOI: 10.1039/d0ra10110a
|View full text |Cite
|
Sign up to set email alerts
|

Low photoactive phase temperature all-inorganic, tin–lead mixed perovskite solar cell

Abstract: In Cs-based all inorganic perovskite solar cells based, doping Sn can cause lattice shrinkage, which reduces annealing temperature of forming photoactive phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…As for the n-i-p architecture, the first p-i-n mixed Sn−Pb PSC was also reported in 2014, with a PCE of around 10% with the perovskite composition of MAPb 0.85 Sn 0.15 X 3 . Since then, significant efforts have been made regarding the optimization of the 3D perovskite composition and stoichiometry, , especially via tuning the ratio of Sn(II) and Pb(II) cations. In the current stage, half Sn(II) and half Pb(II) content for the B-site cation is the most common combination because of its good optoelectronic quality and desirable bandgap for photovoltaic applications, especially as the rear absorber for the all-perovskite tandems . Here, we summarize the results from recent surface modification reports based on the single-junction mixed Sn−Pb PSCs and various related all-perovskite tandems.…”
Section: Interface Engineering For Solar Cellsmentioning
confidence: 99%
“…As for the n-i-p architecture, the first p-i-n mixed Sn−Pb PSC was also reported in 2014, with a PCE of around 10% with the perovskite composition of MAPb 0.85 Sn 0.15 X 3 . Since then, significant efforts have been made regarding the optimization of the 3D perovskite composition and stoichiometry, , especially via tuning the ratio of Sn(II) and Pb(II) cations. In the current stage, half Sn(II) and half Pb(II) content for the B-site cation is the most common combination because of its good optoelectronic quality and desirable bandgap for photovoltaic applications, especially as the rear absorber for the all-perovskite tandems . Here, we summarize the results from recent surface modification reports based on the single-junction mixed Sn−Pb PSCs and various related all-perovskite tandems.…”
Section: Interface Engineering For Solar Cellsmentioning
confidence: 99%
“…This can improve the stability of the photoactive phase at RT, increase the formation energy of point defects, and suppress the generation of point defects. [54][55][56][57] For example, Lee et al fabricated an all-inorganic Sn-rich perovskite material, CsPb 0.4 Sn 0.6 I 2.4 Br 0.6 , with an excellent bandgap of 1.35 eV. 58 The authors investigated the t value and defect formation energy of perovskite materials with different contents of Sn and Pb through DFT simulation.…”
Section: Electronic Band Structurementioning
confidence: 99%
“…This can improve the stability of the photoactive phase at RT, increase the formation energy of point defects, and suppress the generation of point defects. 54–57…”
Section: All-inorganic Psc Devices Based On Mixed Group Iva Cationsmentioning
confidence: 99%
“…The mixed cation halide perovskites (MCHPs) have been suggested as an effective strategy to promote performance and stability and reduce the content of toxic Pb for environmental and health concerns. Large scale experimental and theoretical investigations have confirmed the validity of using mixed metal cations in perovskite materials. The bandgaps of mixed Pb–Sn iodide perovskite absorbers can be tuned continuously from 1.2 to 1.6 eV, leading to potential absorbers for the low-bandgap subcells in tandem solar cells. For example, Kanatzidis et al have explored the binary-metal MAPb 1– x Sn x I 3 and achieved a range of E g from 1.17 to 1.55 eV. , In addition to Pb–Sn MCHPs, another feasible alloying strategy is partial substitution of Pb with Ge cations. Meng et al have found that the incorporation of Ge is a promising way to stabilize CsPbI 3 perovskite solar cells. Sun et al investigated the impact of Pb proportion on the optoelectronic properties of MAGe x Pb 1– x I 3 ( x = 0.25, 0.5, and 0.75), observing a monotonic decrease in bandgap and an increase in visible absorption as the proportion of Pb was gradually reduced. , Moreover, the CsPb 0.95 Ge 0.05 I 3 -based PSC can achieve a certified PCE of 18.8%, which is the highest performance of PSCs based on Pb–Ge MCHPs. , Besides, recent studies have shown that Ge–Sn MCHPs are promising lead-free candidates for light-absorber materials. Chen et al demonstrated that all-inorganic CsGe 0.5 Sn 0.5 I 3 with a bandgap of 1.50 eV was capable of high stability and delivered a PCE of up to 7.11% …”
mentioning
confidence: 99%